Celebrity Endorsement dan Electronic Word of Mouth terhadap Minat Beli pada Serum Anti Aging Garnier di Kota Bandung - Silvia Meilani; Eka Yulianti (Journal of Management and Bussines (JOMB), 2024)
This study aims to analyze the influence of celebrity endorsement and electronic word of mouth on interest in purchasing Garnier anti-aging serum in the city of Bandung. The instrument used in this research was declared to have passed the validity and reliability tests. Furthermore, this instrument was used as a data collection tool for respondents, namely consumers aged at least 17 years who live in Bandung City who are familiar with Garnier anti-aging serum products. This research used a sample of 90 respondents with a purposive sampling method which was considered non-probable. The data analysis techniques used are the classical assumption test, multiple linear regression test, and simultaneous test using SPSS version 26. The results of this study show that 1) celebrity endorsement has a positive and significant effect on purchase interest 2) electronic word of mouth has a positive and significant impact on buying interest. significant influence on purchase interest 3) celebrity endorsement and electronic word of mouth simultaneously influence purchase intention. Keyword: Celebrity Endorsement, Electronic Word Of Mouth, Purchase Itention